2016
DOI: 10.18632/oncotarget.13223
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of long non coding RNAs in non small cell lung cancer: A meta-analysis

Abstract: Background Reports have demonstrated the prognostic function of long non-coding RNAS (lncRNAS) in patients with cancer. However, their prognostic functions in non small cell lung cancer (NSCLC) remain controversial. We therefore performed a meta-analysis on six lncRNAs (PVT1, AFAP1-AS1, LINC01133, ANRIL, MEG3 and UCA1) to clarify their prognostic roles in NSCLC. Results Thirty-six studies involving 6267 patients with NSCLC and 34 lncRNAs were included. Of the listed lnc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…Although numerous molecular markers have been identified for the diagnosis and prognosis of cancer, only a few effective molecular markers can predict the recurrence of NSCLC. Induced lncRNA PVT1 occurred in NSCLC tissues and had a shorter OS time than patients with low PVT1 expression .…”
Section: Discussionsupporting
confidence: 85%
“…Although numerous molecular markers have been identified for the diagnosis and prognosis of cancer, only a few effective molecular markers can predict the recurrence of NSCLC. Induced lncRNA PVT1 occurred in NSCLC tissues and had a shorter OS time than patients with low PVT1 expression .…”
Section: Discussionsupporting
confidence: 85%
“…To improve treatment of patients with NSCLC, novel tumor‐specific biomarkers are needed for diagnosis, targeted therapy, and to predict prognosis LncRNAs are associated with pathological and physiological processes in numerous human cancers. The dysregulated expression of certain lncRNAs has been proven to be associated to proliferation and metastasis in NSCLC . Linc01433 is located on chromosome 20p13 in humans and has a length of 682 bp.…”
Section: Discussionmentioning
confidence: 99%
“…Col‐1, a potent inducer of EMT, regulates the expression of HOTAIR in NSCLC cells, whereas HOTAIR interacts with a chromatin modifier, lymphoid‐specific helicase (LSH), to target genes in NSCLC . Although substantial research of lung‐cancer‐related lncRNAs has been conducted, no lncRNA that can serve as a single molecular marker to diagnose lung cancer has been identified, therefore we need to explore other lncRNAs to obtain a better understanding of this disease. In our previous study, we focused on one of the genes with a change in expression between tumor tissues and matched normal lung tissues, determined by RNA‐sequencing .…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, aberrant expression of multiple lncRNAs were found to be involved in the tumorigenesis and many of them were correlated with cancer prognosis [ 9 11 ]. Multiple lncRNAs have been reported to be promising prognostic indicators for cancers, such as hepatocellular carcinoma [ 12 ], non small cell lung cancer [ 13 , 14 ], osteosarcoma [ 15 ], ovarian carcinoma [ 16 ], and renal cell carcinoma [ 17 ]. So far, many studies have shown that lncRNAs also played critical roles in BC [ 18 ], these findings support that lncRNAs can be developed as novel potential prognostic biomarkers in patients with BC.…”
Section: Introductionmentioning
confidence: 99%